2006
DOI: 10.1123/ijsnem.16.1.65
|View full text |Cite
|
Sign up to set email alerts
|

A Whey-Supplemented, High-Protein Diet versus a High-Carbohydrate Diet: Effects on Endurance Cycling Performance

Abstract: This study compared a training diet recommended for endurance athletes (H-CHO) with an isoenergetic high protein (whey supplemented), moderate carbohydrate (H-Pro) diet on endurance cycling performance. Over two separate 7-d periods subjects (n = 7) ingested either H-CHO (7.9 +/- 1.9 g x kg(-1) x d(-1) carbohydrate; 1.2 +/- 0.3 g x kg(-1) x d(-1) fat; 1.3 +/- 0.4 g x kg(-1) x d(-1) protein) or H-Pro (4.9 +/- 1.8 g x kg(-1) x d(-1); 1.3 +/- 0.3 g x kg(-1) x d(-1); 3.3 +/- 0.4 g x kg(-1) x d(-1)) diet in a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…The slight (NS) decrease in resting diastolic arterial pressure after the high-protein diet is similar to that reported previously (7) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The slight (NS) decrease in resting diastolic arterial pressure after the high-protein diet is similar to that reported previously (7) .…”
Section: Discussionsupporting
confidence: 90%
“…There is evidence that high-protein diets induce a number of favourable changes along with weight loss (reduction in body fat, improvement in lipidaemic and glycaemic profiles and resting blood pressure) (2,4) . The addition of exercise (aerobic and/or resistance) to a high-protein diet had additive effects on body composition during weight loss (5) .Despite the popularity of high-protein diets, few studies have investigated their effects on exercise performance (6,7) . These studies reported that a 7 d high-protein diet decreased endurance (aerobic) performance of recreational and trained athletes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following a high-protein diet compared to high-carbohydrate diet had either a neutral [14] or negative [13] effect on timed trials compared to a high carbohydrate diets. Interestingly, athletes who supplemented with almonds exercised longer than those supplemented with isocaloric cookies, despite the lower carbohydrate content of the almonds [16].…”
Section: Diet Days To Weeks Prior (Adaptive Phase)mentioning
confidence: 99%
“…Macdermid et al investigated the effect of 7 days of a high carb versus a high protein diet on long distance time trial performance in 7 competitive cyclists [13]. They found superior time trial performance in the high carbohydrate group.…”
Section: Carbohydrate Vs Proteinmentioning
confidence: 99%